Diagnosis dan Penatalaksanaan Sialadenitis Bakteri - Wivan Havilian Djohan; Hanggoro Sapto (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2020)
Introductions: Various diseases ranging from obstruction, infection, to benign and malignant tumors occur in the salivary glands. The most common problem is the blockage of the salivary gland ducts which prevents salivary drainage. Objectives: To determine the diagnosis and management of bacterial sialadenitis. Methods: This article was created using the literature review method, involving 30 references in both national and international books and journals. Results: Sialadenitis is inflammation or infection of the salivary glands which can affect the parotid, submandibular and minor salivary glands. Sialadenitis can be caused by infectious or non-communicable factors. Discussions: Bacterial or viral infections are the most frequent etiology. Staphylococcus is a common cause of bacteria, while paramyxovirus is a frequent cause of viruses. Imaging findings in this case vary between enlarged unilateral or bilateral salivary glands, atrophy, abscesses, ductal dilatation, cysts, stones and calcifications. Imaging can detect abscesses in acute bacterial suppurative sialadenitis, ductal changes with cysts in chronic adults and recurrent adolescent parotitis. The correlation of imaging findings with clinical presentation can help diagnose sialadenitis. Post-therapy sialadenitis can occur after the patient has radiotherapy, radioactive iodine or surgery. Conclusions: Proper diagnosis and management of bacterial sialadenitis can prevent complications and a good prognosis. Keywords: Abscess, inflammation, salivary glands, sialadenitis, management